De novo mutations, genetic mosaicism and human disease - Mohiuddin, Mohiuddin; Kooy, R. Frank; Pearson, Christopher E. (Frontiers in Genetics, 2022)
Mosaicism — the presence of genetically distinct populations of cells in a given organism — is an important cause of genetic disease. Mosaicism can appear as de novo DNA mutations, epigenetic alterations of DNA, and chromosomal abnormalities. Neurodevelopmental or neuropsychiatric diseases, including autism—often arise by de novo mutations that are not present in either of the parents. De novo mutations might occur as early as in the parental germline, during embryonic, fetal development, and/or as late as post-natally, through ageing and life. Timing of mutations could lead to mutation loads of less than heterozygosity to approaching homozygosity. Developmental timing of somatic mutation acquirement will affect the mutation load and distribution throughout the body. In this review, we discuss the timing of de novo mutations, spanning from mutations in the germ lineage (all ages), to post-zygotic, embryonic, fetal, and post-natal events, through aging to death. These factors can determine the tissue specific distribution and load of de novo mutations, which can affect disease.